Nanoengineered, magnetically guided drug delivery for tumors: A developmental study - Chen, Tieyu; Kou, Yanyu; Zheng, Ruiling; Wang, Hailun; Liang, Gang (Frontiers in Chemistry, 2022)
Fighting against tumors is always a challenge for medicinal as well as clinical realms. In recent years, surgeries along with chemotherapies have significantly improved the situation and prolonged life expectancy. Theoretically, regardless of dosage, nowadays we have drugs which are strong enough to eliminate most tumors. However, due to the uncontrollable drug distribution, it is difficult to increase the treatment efficiency by simply increasing the drug dosage. Therefore, the preparation of drug delivery system (DDS) that can release ‘bombs’ precisely as much as possible at the target organ or tissue has aroused the researchers’ awareness. In our work, we designed and constructed a silica-based nanocomposite to realize the above demands. The novel nanocomposite drug carrier could be guided to target tumor or tissue by magnetic field since it was built with superparamagnetic Fe3O4 as the core. The Fe3O4 core was continuing cladded with mesoporous silica molecular sieve MCM-41 (represented as MS, in this paper), since MS has enormous ordered hexagonal caves and can offer enough space to hold the drug molecules. To modify the site magnetic-guided carriers into magnetic-guided & light-responsive ones, the benzophenone hydrazone was coupled into the molecular sieve tunnel. When certain wavelength light is imposed to the gating molecules, C=N double bonds will vibrate and swing which will make the cavity that holds the drug molecules change the size and open the tunnels. This makes the nanocomposite have the ability to release loaded drug with light irradiation. The structure, loading abilities as well as the size of the nanocomposite were inspected by scanning electron microscope(SEM), transmission electron microscope(TEM), thermogravimetry analysis (TGA), N2 adsorption/desorption and Dynamic light scattering(DLS).